Detrital zircon U–Pb geochronology of the upper Carboniferous strata of Hala'alat Mountain, West Junggar: implications for provenance. (2nd February 2023) - Chen, Xingyu; Zhang, Zhijie; Yuan, Xuanjun; Liu, Yinhe; Cheng, Dawei; Wan, Li; Zhou, Chuanmin
Abstract: During late Carboniferous time, the residual ocean basin gradually closed in West Junggar and only a small amount of seawater remained in the Hala'alat Mountain area, where discussions of provenance and tectonics are limited. In this study, LA-ICP-MS U–Pb dating and heavy mineral identification are conducted on the upper Carboniferous tuffaceous sandstones from the Hala'alat and Aladeyikesai formations in the Hala'alat Mountain area. The results reveal the low maturity of the clastic sediments, indicating proximal deposition. The Hala'alat Formation detrital zircons present a single peak ( c . 330 Ma). Speculatively, the primary provenance is the Boshchekul–Chingiz Arc, and the secondary sources are the Darbut Tectono-Magmatic Belt and island arcs in the basin. The main peak and provenance of the Aladeyikesai Formation are similar to those of the Hala'alat Formation. Moreover, several age groups, namely, 370–344 Ma, 427–404 Ma and 478–476 Ma, potentially correspond to provenances of the Darbut Tectono-Magmatic Belt, the Boshchekul–Chingiz Arc and the Kujibai–Hongguleleng Ophiolitic Mélange Belt. In addition, the maximum depositional ages of the Hala'alat and Aladeyikesai formations calculated are 314.6 ± 1.54 Ma and 330.8 ± 0.61 Ma, respectively. Comprehensive analysis shows a relatively singular provenance of the Hala'alat Formation. While the provenance of the Aladeyikesai Formation shows inheritance, the provenance area extends northwards to the Kujibai–Hongguleleng Ophiolitic Mélange Belt. Furthermore, the closure of the Junggar Ocean during Carboniferous time caused the potential source region of the Hala'alat Mountain area to migrate northeastwards from Barleik Mountain to Xiemisitai Mountain. This study provides a basis for the analysis of regional geological evolution.